The dilemma of a safe campus: Challenges in preventing and dealing with sexual violence in Indonesian universities - Aulia Nursyifa; Gumilar Rusliwa Somantri; Francisia Saveria Sika Ery Seda (Jurnal Cakrawala Pendidikan, 2026)
This research focuses on identifying obstacles, challenges in preventing and dealing with sexual violence on campus, based on case studies on three campuses in the Greater Jakarta region of Indonesia. The methods used included observation, FGD, interviews, and documentation, with analysis using Publish or Perish, Vos Viewer, and NVivo. The findings of this study show that the issue of sexual violence is a multidimensional and challenging issue: sexual violence is seen as a sensitive issue due to gender stigma; policy implementation needs to pay attention to cultural norms, and social order; campus response is not fast; lack of support of facilities and infrastructure, funds, time and workload, human resources; uneven socialization; Most victims have a hard time proving a case; the perpetrator has a higher power relationship than the victim; other cases of sexual violence: perpetrators of violence by the victim's closest people, cases that occur outside of Tridharma activities, gender-based violence in the digital realm, involving other institutions. Strategies to deal with obstacles and challenges can be carried out in collaboration with all parties (academics, campuses, government, Komnas Perempuan, and so on) in realizing a campus that is safe from the practice of sexual violence.